2023
DOI: 10.3233/shti230547
|View full text |Cite
|
Sign up to set email alerts
|

Automated ML Techniques for Predicting COVID-19 Mortality in the ICU

Abstract: The COVID-19 infection is still a serious threat to public health and healthcare systems. Numerous practical machine learning applications have been investigated in this context to support clinical decision-making, forecast disease severity and admission to the intensive care unit, as well as to predict the demand for hospital beds, equipment, and staff in the future. We retrospectively analyzed demographics, and routine blood biomarkers from consecutive Covid-19 patients admitted to the intensive care unit (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Rahmatinejad et al 7 compared the performance of a variety of regression-based scoring systems, and highlighted the superiority of the APACHE II scoring system in predicting inhospital mortality of patients in the ICU, which was more suitable for critically ill adult patients admitted to the ICU directly from the ED (emergency departments). What sets it apart is the population included in our study, not only the more severe COVID-19 inpatients like in other studies 12 , 23 , 24 but also all COVID-19 inpatients in our hospital. This broad inclusion criterion makes our study less prone to selection bias and improves the generalizability of our findings, as our study has confirmed that our model had higher discrimination in the external dataset demonstrating the generalizability and robustness of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Rahmatinejad et al 7 compared the performance of a variety of regression-based scoring systems, and highlighted the superiority of the APACHE II scoring system in predicting inhospital mortality of patients in the ICU, which was more suitable for critically ill adult patients admitted to the ICU directly from the ED (emergency departments). What sets it apart is the population included in our study, not only the more severe COVID-19 inpatients like in other studies 12 , 23 , 24 but also all COVID-19 inpatients in our hospital. This broad inclusion criterion makes our study less prone to selection bias and improves the generalizability of our findings, as our study has confirmed that our model had higher discrimination in the external dataset demonstrating the generalizability and robustness of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, anemia based on age constitutes one of the six specific objective laboratory test findings used to assess suspicions of incomplete Kawasaki disease [ 59 ], underscoring the significance of the Z score of Hb for the corresponding age in incomplete Kawasaki disease. Moreover, combining the Z score of Hb might be superior to Hb with other clinical markers and may enhance the predictive ability for identifying critical illnesses such as COVID-19 mortality in the ICU [ 60 ], sepsis [ 61 ], and liver disease [ 62 ]. Of course, this synergistic approach has the potential to improve the accuracy and reliability of diagnosing and predicting these severe conditions, allowing for timely intervention and appropriate management strategies.…”
Section: Discussionmentioning
confidence: 99%